2014
DOI: 10.1116/1.4898204
|View full text |Cite
|
Sign up to set email alerts
|

Gettering of hydrogen and methane from a helium gas mixture

Abstract: In this study, the authors developed an approach for accurately quantifying the helium content in a gas mixture also containing hydrogen and methane using commercially available getters. The authors performed a systematic study to examine how both H2 and CH4 can be removed simultaneously from the mixture using two SAES St 172® getters operating at different temperatures. The remaining He within the gas mixture can then be measured directly using a capacitance manometer. The optimum combination involved operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Methane has been shown to decompose at temperatures greater than 650°C into hydrogen and zirconium carbides [15]. Some researchers have indicated that methane removal generally requires temperatures greater than 400°C [16]. Carbon monoxide was not present within these tests but the temperature would likely need to be elevated to prevent deactivation.…”
Section: Figure 2-5: Illustration Of St909 Cracking and Decomposing O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Methane has been shown to decompose at temperatures greater than 650°C into hydrogen and zirconium carbides [15]. Some researchers have indicated that methane removal generally requires temperatures greater than 400°C [16]. Carbon monoxide was not present within these tests but the temperature would likely need to be elevated to prevent deactivation.…”
Section: Figure 2-5: Illustration Of St909 Cracking and Decomposing O...mentioning
confidence: 99%
“…A zirconium, vanadium, iron alloy, ST172, can be operated at various temperatures to achieve varying results [16]. If two beds of the material are operated at 650°C and 110°C, respectively, the first bed will crack methane and the second could be used to getter hydrogen.…”
Section: Temperaturementioning
confidence: 99%